2010
DOI: 10.1080/02648725.2010.10648152
|View full text |Cite
|
Sign up to set email alerts
|

16 years research on lactic acid production with yeast – ready for the market?

Abstract: The use of plastic produced from non-renewable resources constitutes a major environmental problem of the modern society. Polylactide polymers (PLA) have recently gained enormous attention as one possible substitution of petroleum derived polymers. A prerequisite for high quality PLA production is the provision of optically pure lactic acid, which cannot be obtained by chemical synthesis in an economical way. Microbial fermentation is therefore the commercial option to obtain lactic acid as monomer for PLA pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 79 publications
2
94
0
1
Order By: Relevance
“…() demonstrated that the yield of lactic acid changed significantly depending on the strain and LDH gene used. The lactic acid titres achieved in the present study were much lower than those reported in other modified yeast strains (reviewed in Sauer et al ., ), but higher than that for S. cerevisiae W303‐1A transformed with a heterologous LDH (Branduardi et al ., ). It is reported that S. cerevisiae W303‐1A expressing a Bacillus taurus LDH has a lactic acid titre of 20 mg L −1 after 30 h of growth in YNB glucose 2% medium (Branduardi et al ., ).…”
Section: Resultsmentioning
confidence: 83%
“…() demonstrated that the yield of lactic acid changed significantly depending on the strain and LDH gene used. The lactic acid titres achieved in the present study were much lower than those reported in other modified yeast strains (reviewed in Sauer et al ., ), but higher than that for S. cerevisiae W303‐1A transformed with a heterologous LDH (Branduardi et al ., ). It is reported that S. cerevisiae W303‐1A expressing a Bacillus taurus LDH has a lactic acid titre of 20 mg L −1 after 30 h of growth in YNB glucose 2% medium (Branduardi et al ., ).…”
Section: Resultsmentioning
confidence: 83%
“…Although this demonstrated the feasibility of producing d -xylonate with yeast, the titres and rates were low compared to those obtained with bacteria (see above) or for other acids produced in S. cerevisiae , e.g. lactate >100 g l −1 (Sauer et al 2010). …”
Section: Recombinant Yeast For D-xylonate Productionmentioning
confidence: 88%
“…The first paper on metabolic engineering of a yeast strain to produce LA was published in 1994 (Sauer et al, 2010). Candida sonorensis is a methylotrophic yeast that can convert glucose and pentose sugars including xylose and arabinose to ethanol.…”
Section: Lactic Acid Production By Yeastsmentioning
confidence: 99%